Triphenylamine-based luminophores with different side and central aromatic blocks: Synthesis, thermal, photophysical and photochemical properties. (August 2020) - Luponosov, Yuriy N.; Solodukhin, Alexander N.; Balakirev, Dmitry O.; Surin, Nikolay M.; Svidchenko, Eugenia A.; Pisarev, Sergey A.; Fedorov, Yuriy V.; Ponomarenko, Sergei A.
Abstract: In this work, a series of novel luminescent molecules of butterfly-like architecture based on TPA fragments with different central and side aromatic blocks were designed and synthesized. Various properties of the molecules were studied by differential scanning calorimetry, thermogravimetric analysis, UV–Vis optical spectroscopy and compared within this series as well as to their analogs having terminal trimethylsilyl moieties instead of diphenylamine ones. The molecules reported are promising luminescent materials, which combine high thermal stability, good solubility and large molar extinction coefficients with high photoluminescence quantum yields for emission in the green and red spectral regions. The experimental and theoretical investigations reported give more insight to the structure – property correlations for the TPA-based luminophores, as well as to their photostability and peculiarities of the conjugation through triphenylamine units between the central and the side fragments. Graphical abstract: Image 1 Highlights: TPA-based luminophores of different architecture were synthesized and investigated. Molecules combine good stability, solubility, efficient absorption and high luminescence. The work gives more insight to peculiarities of fragments conjugation through TPA units. Linking fragments via TPA units leads to red-shifted absorption and luminescence as compared to Si atom.